Proceedings of the 2021 Conference on Human Information Interaction and Retrieval 2021
DOI: 10.1145/3406522.3446025
|View full text |Cite
|
Sign up to set email alerts
|

Note the Highlight

Abstract: Active reading strategies-such as content annotations (through the use of highlighting and note-taking, for example)-have been shown to yield improvements to a learner's knowledge and understanding of the topic being explored. This has been especially notable in long and complex learning endeavours. With web search This research has been supported by DDS (Delft Data Science) and NWO projects SearchX (639.022.722) and Aspasia (015.013.027).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…All while keeping the user within the familiar search environment. First SAL-oriented explorations propose introducing instructional scaffolding ( Câmara et al, 2021 ), active reading tools ( Roy et al, 2021 ), and assessments ( Urgo and Arguello, 2022 ).…”
Section: Componentsmentioning
confidence: 99%
“…All while keeping the user within the familiar search environment. First SAL-oriented explorations propose introducing instructional scaffolding ( Câmara et al, 2021 ), active reading tools ( Roy et al, 2021 ), and assessments ( Urgo and Arguello, 2022 ).…”
Section: Componentsmentioning
confidence: 99%
“…mind mapping tool or concept map tool) should also be very useful. A recent study by Roy et al [69] investigated the influence of notepad-like interface and interface with highlighting tools on users’ learning performance during a complex, learning-oriented search task. It is found that participants using the interface with highlighting functions enabled covered 34% more subtopics, and participants using the search interface with note taking functions enabled covered 34% more facts in their final essays when compared with a standard web search interface.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Huurdeman, Wilson, and Kamps (2016) pointed out that, without cluttering simple searches, features less commonly found in web search interfaces, when presented at the right moment, could provide value for users. Roy et al (2021) proposed that highlighting and note-taking tools built into the search interface in a SAL environment could help learners cover more facts and subtopics. Ward & Capra (2021) proposed OrgBox as a knowledge representation tool to support complex search tasks by creating SearchIdea, which enabled searchers to actively interact with search results by comparison, prioritization, and rearrangement and was currently introduced by Chavula, Choi, and Rieh (2023), could also be a valuable tool to support learning during search.…”
Section: Research In Search As Learningmentioning
confidence: 99%